Mixed Family Life in the UK : An Ethnographic Study of Japanese-British Families - Nakamura Lopez, M. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book offers a nuanced picture of mixed family life in the UK. Specifically, the book explores how parents from different backgrounds create a place of belonging for their children, while also negotiating difference and attempting to transmit various aspects of their cultures, including religion, hobbies, language and food to their mixed children. Based on data collected from 26 months of fieldwork, the author concludes that the intergenerational transmission of culture, instead of being tied to the idea of "national culture", is actually more organic and fluid, allowing individuals to share their "cultures", from traditions and customs to preferences and habits, with the next generation. As mixedness increasingly becomes the norm in our global society, the book will be of interest to students and scholars of race, ethnicity and family studies, as well as social workers, school teachers, counsellors, and parents and kin of mixed children.
Keywords: Social sciences.; Ethnology -- Asia.; Ethnicity.; elektronické knihy; electronic books